2011
DOI: 10.1260/0263-0923.30.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vehicle Size, Haulage Capacity and Ride Control on Vibration Exposure and Predicted Health Risks for LHD Vehicle Operators

Abstract: Documented whole-body vibration (WBV) exposure levels at the operator/seat interface are limited for underground mining load-haul-dump (LHD) vehicles. Therefore, WBV exposure during the operation of eight small and nine large LHD vehicles, under loaded and empty haulage, was measured in accordance with ISO 2631-1 guidelines. Vibration exposure was also measured for a subsample of LHD vehicles equipped with a feature designed to reduce vibration exposure (ride-control).Operator health risks were predicted accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
5
22
0
Order By: Relevance
“…The vibration transmitted to the hand-arm through contact with the controls of vehicles or the steering wheel is not relevant (Hill, Langis et al 2001;Donoghue 2004;Gallagher and Mayton 2007;Kunimatsu and Pathak 2012). However, these workers are exposed to impact shocks (Eger, Stevenson et al 2011). The bibliography, focused on WBV, follows almost consensually, the ISO standard 2631-1:1997 -Mechanical vibration and shock -Evaluation of human exposure to whole-body vibration -Part 1: General requirements (ISO 1997).…”
Section: Methodologies Applied To the Measurement Of Vibrations Transmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibration transmitted to the hand-arm through contact with the controls of vehicles or the steering wheel is not relevant (Hill, Langis et al 2001;Donoghue 2004;Gallagher and Mayton 2007;Kunimatsu and Pathak 2012). However, these workers are exposed to impact shocks (Eger, Stevenson et al 2011). The bibliography, focused on WBV, follows almost consensually, the ISO standard 2631-1:1997 -Mechanical vibration and shock -Evaluation of human exposure to whole-body vibration -Part 1: General requirements (ISO 1997).…”
Section: Methodologies Applied To the Measurement Of Vibrations Transmentioning
confidence: 99%
“…Other parameters analyzed in WBV studies are: machines characteristics (Kumar 2004;Howard, Sesek et al 2009;Eger, Stevenson et al 2011;Dentoni & Massacci 2013); operations that the equipment performs (Kumar 2004;Eger, Stevenson et al 2008;Salmoni, Cann et al 2010;Smets, Eger et al 2010;Leduc, Eger et al 2011); work routines (Torma-Krajewski, Wiehagen et al 2009;Smets, Eger et al 2010); pavement conditions (Mayton, Amirouche et al 2005;Howard, Sesek et al 2009;Salmoni, Cann et al 2010;Dentoni & Massacci 2013); position and seat features (Mayton, Amirouche et al 2005); vibration type (continuous, intermittent, impact) and its direction and source (Leduc, Eger et al 2011); number of times that performs the task or all work cycle per day, average duration of the task or work cycle (Mandal & Srivastava 2010;Smets, Eger et al 2010); Simultaneously, other important information are collected as e.g. demographic information, medical and occupational historic and lifestyle (Eger, Stevenson et al 2008;Mandal & Srivastava 2010;Smets, Eger et al 2010;Eger, Stevenson et al 2011;Leduc, Eger et al 2011).…”
Section: Methodologies Applied To the Measurement Of Vibrations Transmentioning
confidence: 99%
“…For example, in a study of large LHD operators Eger and colleagues found an operator's musculoskeletal injury risk score to be correlated with greater vibration exposure, poor working postures and higher levels of spinal compression [18]. It is also important to remember WBV exposure and the associated risk of musculoskeletal injury are also dependent on other factors such as driving speed, road surface, backrest contact, and muscle fatigue [10,19,20].…”
Section: Vibration Exposure and Musculoskeletal Injurymentioning
confidence: 99%
“…The workplace vibration levels in underground hard-rock mining often exceed the ISO 2631-1 HGCZ [15,[21][22][23][24]. One recent study showed that the HGCZ was exceeded in all 8 small load-haul dump vehicles (LHDs; <3 m 3 bucket haulage capacity) and in one of the nine large LHDs (>3 m 3 bucket haulage capacity) [22].…”
Section: Introductionmentioning
confidence: 99%
“…The workplace vibration levels in underground hard-rock mining often exceed the ISO 2631-1 HGCZ [15,[21][22][23][24]. One recent study showed that the HGCZ was exceeded in all 8 small load-haul dump vehicles (LHDs; <3 m 3 bucket haulage capacity) and in one of the nine large LHDs (>3 m 3 bucket haulage capacity) [22]. Haulage truck operators in surface mining operations also regularly exceed the ISO 2631-1 HGCZ [15,23], and one study that evaluated 20 different mining vehicle operations found that five were within the HGCZ and seven exceeded the HGCZ [10].…”
Section: Introductionmentioning
confidence: 99%